Performance evaluation of China's industry: a generalized equilibrium data envelopment analysis approach with fixed-sum undesirable output. Issue 2 (3rd May 2021) - Yang, Min; An, Qingxian; Hu, Dan; Liang, Liang
Abstract: With the rapid development of economy, China faces a considerable challenge from environmental problems especially with the waste of gas pollution emitted by China's industry. To assess the environmental performance of China's industry, this paper proposes a new generalized equilibrium efficiency frontier data envelopment analysis (GEEFDEA) approach that considers waste gases as undesirable outputs. It is assumed that the total amount of waste gases that the industry is permitted to emit is limited (or fixed), that is, increasing air pollution of one area should reduce that of other areas for offset. Compared with the prior evaluation approaches, the proposed approach is the only one that satisfies the following conditions simultaneously. 1) The approach considers the property of the "fixed sum" of undesirable outputs. 2) The approach avoids the case in prior approaches (e.g., fixed sum output and zero sum gains DEA approaches) that an infeasible solution may occur when accessing decision making unites (DMUs) with fixed-sum undesirable outputs. 3) The proposed approach inherits all advantages of the GEEFDEA approach such as achieving an equilibrium state by only one step and obtaining a complete ranking order. Finally, the proposed approach is applied to evaluate the performance in China's industry from 2008 to 2013. Results show China's industry has significant regional characteristics.